Des stéréotypes à l’ère des fake news - Isabelle Boyer; Luciana Radut-Gaghi (Communication)
The authors explore synergies in the operation of two pairings: news/fake news and social representation/stereotype. In the context of current public debate in which fake news is blended with real news, climate issues are fertile ground for research on the polemical use of stereotypes in the definition of self and the relationship to the other. The public’s suspicious mood lends itself to an analysis of the figure of the scientist as it has emerged in the dialogue between climate defenders and climate skeptics. The corpus is made up writings by recognized scientists published in French that have become references in the field in the last 15 years.